Impact of Baseline Anemia in Patients With Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention: A Prespecified Analysis From the VALIDATE‐SWEDEHEART Trial. Issue 16 (20th August 2019) - Wester, Axel; Attar, Rubina; Mohammad, Moman Aladdin; Andell, Pontus; Hofmann, Robin; Jensen, Jens; Szummer, Karolina; Erlinge, David; Koul, Sasha
Abstract : Background: The impact of baseline anemia in a contemporary acute coronary syndrome (ACS) population undergoing percutaneous coronary intervention in the era of predominant radial artery access, potent P2Y12 inhibition, and rare use of glycoprotein IIb/IIIa inhibitors has not been adequately studied. Methods and Results: ACS patients who underwent percutaneous coronary intervention between 2014 and 2016 in the VALIDATE‐SWEDEHEART (Bivalirudin Versus Heparin in ST‐Segment and Non–ST‐Segment Elevation Myocardial Infarction in Patients on Modern Antiplatelet Therapy in the Swedish Web System for Enhancement and Development of Evidence‐Based Care in Heart Disease Evaluated According to Recommended Therapies Registry) trial without missing values for hemoglobin were included (n=5482). Mortality, myocardial reinfarction, and major bleeding at 180 days were assessed using Cox regression models and propensity score matching. All studied comorbidities were more common in ACS patients who had anemia (n=792). ACS patients with anemia had higher rates of 180‐day mortality (6.9% versus 2.1%; hazard ratio, 1.9; 95% CI, 1.3–2.7; P <0.001), myocardial reinfarction (4.3% versus 1.9%; hazard ratio, 1.7; 95% CI, 1.1–2.7; P =0.013), and major bleeding (13.4% versus 8.2%; hazard ratio, 1.3; 95% CI, 1.0–1.6; P =0.041). The results were most evident in patients with a hemoglobin value <100 g/L, who had a nearly 10 times higher mortality rate. Conclusions: Baseline anemia in ACS patients undergoing percutaneous coronary intervention, treated according to current practice including routine radial artery access, constitutes a high‐risk feature for both ischemic events, bleeding events, and mortality. A multidisciplinary approach is warranted to maximize benefit and minimize patient risk. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02311231.